2007
DOI: 10.1016/j.neuron.2007.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Firing among Retinal Ganglion Cells Signals Motion Reversal

Abstract: We show that when a moving object suddenly reverses direction, there is a brief, synchronous burst of firing within a population of retinal ganglion cells. This burst can be driven by either the leading or trailing edge of the object. The latency is constant for movement at different speeds, objects of different size, and bright versus dark contrasts. The same ganglion cells that signal a motion reversal also respond to smooth motion. We show that the brain can build a pure reversal detector using only a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 46 publications
(59 reference statements)
4
121
0
Order By: Relevance
“…The internal functional architecture of our models match that of the retina at the level of individual neurons, and moreover our models generalize from natural scenes, but not white noise, to a wide range of artificially structured stimuli with vastly different statistics. Thus this work provides quantitative validation for the deep learning approach to neuroscience in an experimentally accessible sensory circuit, places decades of work [7][8][9][10][11][12][13][14][15] on retinal responses to artificially structured stimuli on much firmer foundations of ethological relevance, and highlights the fundamental importance of studying sensory circuit responses to natural stimuli.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The internal functional architecture of our models match that of the retina at the level of individual neurons, and moreover our models generalize from natural scenes, but not white noise, to a wide range of artificially structured stimuli with vastly different statistics. Thus this work provides quantitative validation for the deep learning approach to neuroscience in an experimentally accessible sensory circuit, places decades of work [7][8][9][10][11][12][13][14][15] on retinal responses to artificially structured stimuli on much firmer foundations of ethological relevance, and highlights the fundamental importance of studying sensory circuit responses to natural stimuli.…”
mentioning
confidence: 79%
“…3A), latency encoding 10 (Fig. 3B), synchronized responses to motion reversal 11 (Fig. 3C), motion anticipation 12 (Fig.…”
Section: Cnns Replicate Wide Range Of Retinal Phenomenamentioning
confidence: 98%
“…Second, correlated activities of retinal neurons drive their common post-synaptic neurons in lateral geniculate nucleus (LGN) more effectively and efficiently because of spatial summation (Usrey et al, 1998;. Third, it is also reported that correlated activities are related to some specific functions of retina, such as color discrimination (Chen et al, 2004) and motion detection (Schwartz et al, 2007).…”
Section: The Significance Of Correlated Firings Among Neuronsmentioning
confidence: 99%
“…One possibility is that object motion is detected as early the retina, where a subset of retinal ganglion cells (RGCs) respond to differential motion of their receptive field center and surround (Olveczky et al, 2003;Zhang et al, 2012). However, these cells, like RGCs that respond to motion onset or reversal (Schwartz et al, 2007;Chen et al, 2013) or RGCs that are tuned to movement speed and direction (Oyster, 1968), also respond to the sudden appearance/disappearance of stationary stimuli and therefore do not specifically signal object motion.…”
Section: Introductionmentioning
confidence: 99%